A Smoothing Technique For Objective Penalty Function In Inequality Constrained Optimization (Journal of Namibian Studies : History Politics Culture, 2023)
This manuscript provides a smoothing technique for objective penalty functions in inequality constrained optimization problems. A non- smooth penalty function is defined which is subjected to new smoothing technique to make it smooth. The error estimates for the original and the smoothed problem are discussed. A procedure is illustrated for the development of the solution of the inequality constrained optimization problem and is shown to be convergent under certain specified conditions.